Detached Eddy Simulation on Hypersonic Base Flow Structure of Reentry-F Vehicle. (2015) - Zhi, Chen; Liang, Zhang; Pengfei, Li
Abstract: A detached eddy simulation of Reentry-F flight vehicle is conducted to investigate its base flow structure. The result shows that DES predicts more accurate heat transfer rates compared to the flight experiment data than laminar and RANS (Spalart-Allmaras model) simulations. The initial vortex surface of base flow field is of toroidal shape, but the decrease of recirculation region cross section area forces the vortex surface first to shrink, then breakdown and reunite, and finally curl to several x-axis elongated vortex surfaces. These x-axis elongated vortex surfaces are origin for the strips distribution of temperature contour on the z=0 plane.